نفقة المتعة في التشريعين الجزائري والمصري - شامي, أحمد (جامعة الوادي University of Eloued, 2018)
تعالج هذه الورقة البحثية نفقة المتعة في التشريعين الجزائري والمصري، حيث أن وقوع الطلاق بين الزوجين قد يسبب أضرارا للمطلقة، والطلاق مهما كانت أسبابه، ولو كانت المطلقة هي المتسببة فيه، غالبا ما تُصاحبه آلام نفسية تعاني منها الزوجة المطلقة. وجبرا لخاطر المطلقة، وتخفيفاً لوحشتها، فُرض لها مبلغ من المال إن على سبيل التطوع والاستحباب، أو على وجه التحتيم والإلزام، يدفعه الزوج لها بعد طلاقها، والذي يسمى بنفقة المتّعة. فالمشرع الجزائري لم يتطرق لنفقة المتعة، ولكن بالرجوع لأحكام المادة 222 من قانون الأسرة والتي تحيلنا إلى أحكام الشريعة الإسلامية، نرى بأن المشرع ترك الأمر للاجتهاد القضائي الذي أكد على إيجاب المتعة شرعا، وتقرير الحق في التعويض قانونا، وهذا لا يستقيم لاختلاف موجب كل من المتعة والتعويض، فإن اتحدا في الحكمة فقد اختلفا في السبب، ومن ثم يكون لكل منهما حكمه الخاص. بخلاف المشرع المصري الذي نص صراحة على أن نفقة المتعة تعتبر من آثار الطلاق وذلك من خلال المادة 18 مكرر من القانون رقم 100 لسنة 1985. This document deals with the expense of pleasure in the Algerian and Egyptian legislations. Divorce between the spouses may cause harm to the divorcee and divorce regardless of its causes, even if the divorced woman is the cause of the divorce, often accompanied by psychological pain suffered by the divorced wife. And to pay for the absolute risk, and the alleviation of her shame, to impose a sum of money, whether for volunteering and implication, or on the face of infidelity and obligation, paid by the husband after her divorce, which is called maintenance of pleasure. The Algerian legislator did not address the expense of pleasure, but by reference to the provisions of Article 222 of the Family Code, which refer us to the provisions of Islamic law, we see that the legislator left the jurisprudence of the jurisprudence, which emphasized the pleasure of the law and the right to compensation law, and this is not true for the difference of positive pleasure And compensation, if they united in wisdom they differed in the cause, and then each of them had his own judgment. Unlike the Egyptian legislator who explicitly stated that the expense of pleasure is considered the effects of divorce, through article 18 bis of Law No 100 of 1985.
Keywords: طلاق ؛ أضرار ؛ اجتهاد القضائي ؛ مبلغ من المال ؛ نفقة المتعة